Migrant memory B cells secrete luminal antibody in the vagina - Oh, Ji Eun; Iijima, Norifumi; Song, Eric; Lu, Peiwen; Klein, Jonathan; Jiang, Ruoyi; Kleinstein, Steven H.; Iwasaki, Akiko (Nature (London), 2019)
Antibodies secreted into mucosal barriers serve to protect the host from a variety of pathogens, and are the basis for successful vaccines 1 . In type I mucosa (such as the intestinal tract), dimeric IgA secreted by local plasma cells is transported through polymeric immunoglobulin receptors 2 and mediates robust protection against viruses 3 , 4 . However, owing to the paucity of polymeric immunoglobulin receptors and plasma cells, how and whether antibodies are delivered to the type II mucosa represented by the lumen of the lower female reproductive tract remains unclear. Here, using genital herpes infection in mice, we show that primary infection does not establish plasma cells in the lamina propria of the female reproductive tract. Instead, upon secondary challenge with herpes simplex virus 2, circulating memory B cells that enter the female reproductive tract serve as the source of rapid and robust antibody secretion into the lumen of this tract. CD4 tissue-resident memory T cells secrete interferon-γ, which induces expression of chemokines, including CXCL9 and CXCL10. Circulating memory B cells are recruited to the vaginal mucosa in a CXCR3-dependent manner, and secrete virus-specific IgG2b, IgG2c and IgA into the lumen. These results reveal that circulating memory B cells act as a rapidly inducible source of mucosal antibodies in the female reproductive tract. In a mouse model of herpes simplex 2 virus infection, circulating memory B cells—rather than plasma cells—are shown to be the source of antibody secretion in the vaginal lumen following secondary infection.